CulTraB. mobile learning app / Nurul Azrin Ariffin ... [et al.] - Ariffin, Nurul Azrin; Mohd Daud, Norzaidi; Jamaludin, Nor Lelawati; Mohamed, Munirah; Hashim, Nurhaslinda (Universiti Teknologi MARA, Kedah, 2024)
Quizzes provide an opportunity to practice one’s knowledge without failure and fear. Thus, this leads to the invention of CulTraB. to allow individuals to improve their knowledge through interactive quizzes provided in this App. For stater, this App contains two quizzes which are the Consumer Centrism Group (CCG) quiz and Personality Traits (PT) Quiz. The aim of CulTraB. is to boost one’s knowledge in a stress-free way of learning through series of interactive quizzes. Mobile learning apps offer flexibility and convenience to the users of CulTraB. who can actively participate in the readily available quizzes at their own convenience. The quizzes submissions by the users allow CulTraB. to form data visuals which can benefit the marketers if they are interested so that they can strategize their businesses accordingly. CulTraB. also help in saving the environment since this App provides paperless quizzes, thus, promoting sustainability. The commercialization potential lies in the data visuals for the marketers and advertisement as the common monetization strategy in which CulTraB. will offer ad space to advertisers to display targeted ads to the users. In future more quizzes will be added to this App to offer users with exciting and informative contents.